2009
DOI: 10.1038/jcbfm.2009.181
|View full text |Cite
|
Sign up to set email alerts
|

Induction Profile of MANF/ARMET by Cerebral Ischemia and its Implication for Neuron Protection

Abstract: Cerebral ischemia-induced accumulation of unfolded proteins in vulnerable neurons triggers endoplasmic reticulum (ER) stress. Arginine-rich, mutated in early stage tumors (ARMET) is an ER stress-inducible protein and upregulated in the early stage of cerebral ischemia. The purposes of this study were to investigate the characteristics and implications of ARMET expression induced by focal cerebral ischemia. Focal cerebral ischemia in rats was induced by right middle cerebral artery occlusion with a suture; isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 36 publications
4
95
0
Order By: Relevance
“…MANF was identified as a secreted protein from a cell line of astrocyte origin (1); however, subsequent studies found that neurons express the highest levels of MANF in the brain (12,39). MANF is also expressed in non-neuronal tissue, with widespread distribution and the highest expression generally found in tissues with a large secretory function, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…MANF was identified as a secreted protein from a cell line of astrocyte origin (1); however, subsequent studies found that neurons express the highest levels of MANF in the brain (12,39). MANF is also expressed in non-neuronal tissue, with widespread distribution and the highest expression generally found in tissues with a large secretory function, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…It is suspected that the different localization of CHOP depends on the state of the cells and the intensity of the stress effect (56). In wt virus-infected cells, CHOP was detected in the nuclei of the majority of the cells, indicating severe ER stress, while in SAT Ϫ virus-infected cells, CHOP was also expressed, but to a lesser extent (41% of SAT Ϫ virus-infected cells versus 76% of wt-infected cells), and its localization remained perinuclear (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, it has been reported that the expression of CRELD2 and MANF are elevated in several physiological conditions, which are not restricted to the central nervous system. 23,[37][38][39] Therefore, further characterization of MANF and CRELD2 inside and outside cells under pathophysiological conditions may give new insights into the onset and progression of ER stress-related diseases. Fig.…”
Section: Discussionmentioning
confidence: 99%